2016
DOI: 10.1039/c6ra24275h
|View full text |Cite
|
Sign up to set email alerts
|

Multispectroscopic analysis and molecular modeling to investigate the binding of beta lactoglobulin with curcumin derivatives

Abstract: Bovine beta lactoglobulin (β-lg), the major whey protein, has a great affinity for a wide range of organic compounds like fatty acids, retinol etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Curcumin located near Trp19, Tyr20, Thr125, Pro126, Glu158 and Glu44 through both hydrophobic interactions and hydrogen bonds, which was similar to the binding site in b-lg-resveratrol and b-lg-isoxazole interactions. 39,40 Moreover, the binding mode for curcumin out of the b-lg calyx was still stable when solvation and exibility was present in the biological system (Fig. S6 †).…”
Section: Binding Behaviors In the Formation Of The Ternary Complexesmentioning
confidence: 99%
“…Curcumin located near Trp19, Tyr20, Thr125, Pro126, Glu158 and Glu44 through both hydrophobic interactions and hydrogen bonds, which was similar to the binding site in b-lg-resveratrol and b-lg-isoxazole interactions. 39,40 Moreover, the binding mode for curcumin out of the b-lg calyx was still stable when solvation and exibility was present in the biological system (Fig. S6 †).…”
Section: Binding Behaviors In the Formation Of The Ternary Complexesmentioning
confidence: 99%
“…For β-lg, it is possible to bind PADs inside its hydrophobic calyx, which is unfolding/exposing at the interface. Possible amino acids in the calyx for π-interactions are Phe 105 , Asn 90 , Ile 84 , Ile 56 , Val 43 , Val 92, and Met 107 residues [29]. Interactions in the calyx may have an important impact on the adsorption and unfolding behavior of β-lg at the interface as demonstrated in this study.…”
Section: Pendant Drop Tensiometer Interfacial Tension Of Pad-proteinmentioning
confidence: 54%
“…In the present study, β-lactoglobulin was used as a model protein since its interfacial behavior is well characterized. Previous studies on β-lactoglobulin and phenolic compound (curcumin) (reference) showed that hydrogen bonds, π-stacking, and other π-interactions like π-alkyl, π-anion, and π-sigmaas a kind of hydrophobic interactionsare the main forces for this proteinphenol bonding [29].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the fluorescence intensity of the protein was found to depend on the concentration of 4 which was analyzed by using the Stern–Volmer plots. Thus, the plots of F 0 /F versus concentration of 4 gave a straight line with an intercept as shown in the insets of the plots given in the Supporting Information (SI) (where F 0 is the fluorescence intensity at λ max without addition of 4 and F is the fluorescence intensity at λ max with different concentrations of 4 ) ,. From this plot, for the compounds 4 c (shown in the inset of Figure ) the binding constants was calculated to be 16.3×10 5 M −1 .…”
Section: Resultsmentioning
confidence: 99%